1989
DOI: 10.1159/000226684
|View full text |Cite
|
Sign up to set email alerts
|

Carcinogenic Effect of Biscuits Made of Flour Infested with <i>Tribolium castaneum</i> in <i>Bufo regularis</i>

Abstract: Biscuits made of flour infested with Tribolium castaneum induced the formation of hepatocellular carcinomas (22%) when force-fed to toads (Bufo regularis) at a dose level of 200mg/50g 3 times a week. Maximal time of exposure and observation was 16 weeks. Some metastatic deposits from the primary liver tumours were found in the kidneys. Thus, the carcinogenic potency of the biscuits was almost the same as that of the flour previously reported by the authors indicating that the temperature of the oven in which t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 5 publications
0
6
0
2
Order By: Relevance
“…El-Mofty et al [4,6,34] reported that, baking temperature did not reduce the carcinogenic effect of biscuits made from flour infested with T. castaneum beetles but the mutagenic effects on mice remains unclear after being contaminated flour had been cooked and consumed, and Tribolium spp. are the only storage pests producing carcinogenic and teratogenic contaminants.…”
Section: Effect Of T Castaneum Adult Emergence On Bqs (Sum Both Of Mmentioning
confidence: 99%
“…El-Mofty et al [4,6,34] reported that, baking temperature did not reduce the carcinogenic effect of biscuits made from flour infested with T. castaneum beetles but the mutagenic effects on mice remains unclear after being contaminated flour had been cooked and consumed, and Tribolium spp. are the only storage pests producing carcinogenic and teratogenic contaminants.…”
Section: Effect Of T Castaneum Adult Emergence On Bqs (Sum Both Of Mmentioning
confidence: 99%
“…In a follow-up study, El-Mofty et al (1989) investigated the effect of infested flour in biscuits fed to tadpoles and biscuit baking temperature on the carcinogenic properties of flour. Similarly to the previous experiment, tadpoles were divided into two groups.…”
Section: Carcinogenicity and Toxicitymentioning
confidence: 99%
“…6,7 The presence of uric acid is an indication of insect infestation and is reported as carcinogenic, which ultimately spoils the quality of flour. 8 In addition to contamination with body fragments and frass, flour is often exposed to quinones that the adult insects secrete as defensive mechanisms. 9 These quinones are responsible for an unpleasant odour and are known to induce liver and spleen tumours when tested in rats and other vertebrates.…”
Section: Introductionmentioning
confidence: 99%